Strigolactone Involvement in Root Development, Response to Abiotic Stress, and Interactions with the Biotic Soil Environment. Issue 2 (18th July 2014) - Kapulnik, Yoram; Koltai, Hinanit
Abstract : Strigolactones play a role in root development, root response to nutrient deficiency, and plant interactions in the rhizosphere . Abstract: Strigolactones, recently discovered as plant hormones, regulate the development of different plant parts. In the root, they regulate root architecture and affect root hair length and density. Their biosynthesis and exudation increase under low phosphate levels, and they are associated with root responses to these conditions. Their signaling pathway in the plant includes protein interactions and ubiquitin-dependent repressor degradation. In the root, they lead to changes in actin architecture and dynamics as well as localization of the PIN-FORMED auxin transporter in the plasma membrane. Strigolactones are also involved with communication in the rhizosphere. They are necessary for germination of parasitic plant seeds, they enhance hyphal branching of arbuscular mycorrhizal fungi of the Glomus and Gigaspora spp., and they promote rhizobial symbiosis. This review focuses on the role played by strigolactones in root development, their response to nutrient deficiency, and their involvement with plant interactions in the rhizosphere.